Relationship between climatic factors and initiation of red rot infection in sugarcane - and RAM NIWAS2, ANIL KUMAR1, SATYAVIR1 (Indian Phytopathology, 2002)
During 1994-95 and 1995-96 susceptible sugarcane cv. Co 7117 was planted in Hisar, Haryana, India. Canes were inoculated with Colletotrichum falcatum [Glomerella tucumanensis] through nodal inoculation and the correlation between red rot initiationand climate was investigated. It is suggested that red rot infection was highly influenced by climate and that the resulting regression models can be used to forecast red rot initiation in sugarcane.